The Market Size for Carbon Negative Replacements of Gasoline and Diesel Fuel and the Manufacture of the Carbon Negative Mixtures - Tyurin, Michael (Jour Med Resh and Health Sci, 2024)
We established in this original article that the numbers per the manufacture of the Carbon Negative fuel mixtures to replace Gasoline and Diesel fuels produced from petroleum has to be slightly larger in numbers that the actual numbers of the consumed Carbon Negative fuels to reduce substantially the air CO2 which causes fresh water loss to the Space vacuum. The catch is that if we want to decrease the air CO2 content we have to manufacture more Carbon Negative fuels then the amount of them consumed. We want to start from the Carbon Negative fuels manufacture at the level of $380 billion at the market size of 2023. This number must be higher later on depending on the rate of the inflation and the growth rate of the fuel markets. Key Words: